Does political connection and family business create or destroy firm performance: lesson learnt from Malaysia / Fazrul Hanim Abd Sata … [et al.] - Abd Sata, Fazrul Hanim; Azmi, Nurul Azlin; Sukar, Muhamad Ashaari; Mohd Suffian, Mohd Taufik; Yendrawati, Reni; Zakaria, Nor Balkish (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2023)
This study examined the effect of the family business on firm performance and whether the political connection moderates these relationships. Final sample consisted of 1,969 firm-year observations from 2013 - 2017. Family characteristics and political connections data were hand-collected from annual report and financial data were extracted from Eikon Datastream. We found that family chairmanship and high family ownership concentration can destroy firm performance, exhibited by low Tobin Q. However, the moderating effect of political connection between family business and firm performance showed a positive and significant association. This implies that politicians in the family firm can create firm performance as they can work as external watchdogs. Additional analysis showed that political connections in high family ownership can destroy firm performance. These findings provide practical implications for regulators and investors that they should be mindful of the designation of family members and appointment of politicians in firms as it may create agency costs and destroy firm performance. This study adds to the limited, albeit important evidence on the joint effect of politically connected firms and family businesses on firm performance.